Benzocaine and eugenol as anesthetics for Brycon hilarii - doi: 10.4025/actascianimsci.v35i2.16644 - Fabiani, Bruno Matucita; Boscolo, Wilson Rogério; Feiden, Aldi; Diemer, Odair; Bittencourt, Fábio; Neu, Dacley Hertes (Acta Scientiarum. Animal Sciences, 2012)
Anesthetic products are frequently employed during fish handling practices; however, the correct doses of the various chemicals for different species are still unknown. This study determined the ideal concentrations of benzocaine and eugenol as anesthetics used in Brycon hilarii juveniles. The fish were acquired from a commercial fish farm located in western Paraná state, Brazil, totaling 104 juveniles, with average body weight and length of 50.04 ± 20.80 g and 16.30 ± 12.32 cm respectively. The study was carried out at the Aquiculture Laboratory from the Aquaculture Management Study Group - GEMAq at the West Parana State University. Five benzocaine concentrations (50.0, 100.0, 150.0, 200.0 and 250.0 mg L-1) and seven eugenol concentrations (50.0, 100.0, 150.0, 200.0, 250.0, 300.0 and 350 mg L-1) were evaluated in order to assess the induction time to anesthesia. The fish were transferred to anesthetic-free tanks to recover, and the time needed to return to normal activity was recorded. The best results were observed with the benzocaine dose of 100 mg L-1 and the eugenol dose between 100 and 150 mg L-1.